Participants' assessment towards Human Development Adult Education Program in Malaysia - Ahmad, Abdul Razaq; Zainal Abiddin, Norhasni; Wan Mamat, Wan Hasmah (Journal of International Social Research, 2009)
Adult education has been sidelined by mainstream educational researchers in Malaysia. The purpose of this article was to survey the effect of Society Development Department (KEMAS) adult education from the participants’ perspectives. The focus was on the participants’ achievements in cognitive, affective, and skill in the KEMAS programs especially in Human Development. Human intellectual is an important resource to develop a country. Thus, this study was used to focus on human development through continuous learning to fulfill the objectives. Based on Hammond theory (1973) that emphasized on the importance of participants’ input in program evaluation. The total participants in this study comprised 1,563 adults who participated in the Civic Development Program in four states in Malaysia - Pahang (502 adults), Perak (512 adults), Negeri Sembilan (302 adults) and Johor (247 adults). The survey showed that the participants have higher achievement in skill in the Human Development Program. Human Development Program can also emphasize on universality issues which include the relationship between knowledge and social. Besides that, society accountability should take into account. It is suggested that a comprehensive assessment should be focus more on andragogy.